Di-(2-ethyl hexyl) phthalate induced oxidative stress promotes microplastics mediated apoptosis and necroptosis in mice skeletal muscle by inhibiting PI3K/AKT/mTOR pathway. (30th May 2022) - Liu, Xiaojing; Zhang, Yilei; Sun, Xinyue; Zhang, Wenyue; Shi, Xu; Xu, Shiwen
Abstract: The plastic decomposition product microplastics (MPs) and the plastic additive Di (2-ethylhexyl) phthalate (DEHP) in the environment can damage various organs of the organism by inducing oxidative stress. The PI3K/AKT/mTOR signaling pathway participate in toxin-induced apoptosis and necroptosis. However, the effects of DEHP/MPs alone and combined exposure on skeletal muscle cell injury in mice and the role of PI3K/AKT/mTOR axis remain unclear. To investigate the effect of DEHP or/and MPs on skeletal muscle in mice and its possible toxicological mechanism, 60 mice were randomly divided into control group, DEHP group (DEHP 200 mg/kg dissolved in 50 mL corn oil mixed with 2.5 kg diet), MPs group (10 mg/L MPs in drinking water) and combined exposure group. In vitro, C2C12 cells were exposed to DEHP 600 μM/MPs 800 μM alone or in combination for 24 h. The results showed that DEHP/MPs exposure alone or in combination increased MDA content, decreased activities of CAT, T-AOC, SOD and GSH-Px, increased mRNA and protein expressions of Caspase-3, BAX, RIPK1, RIPK3 and MLKL, and decreased BCL-2 expression. The expression of PI3K/AKT/mTOR signaling pathway was significantly down-regulated. All the above results showed that the combined exposure group was more toxic, and similar experimental results were obtained by DEHP/MPs exposure test of C2C12 cells in vitro. It is suggested that DEHP/MPs can induce apoptosis and necroptosis by activating oxidative stress and down-regulating PI3K/AKT/mTOR pathway. This study provides new evidence for clarifying the possible mechanism of toxicity of DEHP and MPs to skeletal muscle of mice. Graphical Abstract: ga1 Highlights: DEHP/MPs exposure induces apoptosis and necroptosis in mouse skeletal muscle. DEHP/MPs exposure activated oxidative stress and decreased the expression of PI3K / AKT / mTOR pathway. DEHP combined with MPs exposure aggravates skeletal muscle injury in mice.